Features of the Use of Addressed Statements in Russian Orthodox Sermon - V. A. Burtsev (Научный диалог, 2020)
The features of the use of addressed utterances are considered from the point of view of the concept of asubjectivation, as opposed to the locuous activity of the subject of speech. Asubjectivation is defined as the presence in the semantics of the statement of the point of view of a non-assertive judgment subject, which is not perceived by the speaker’s sphere of consciousness and imposes restrictions on the meaning of the illocutionary act. The main method for identifying and describing asubjectivation in addressed utterances in a sermon is the identification of the scope and illocutionary force of the utterance. It has been proven that addressed utterances in a sermon, regardless of the speaker’s intentions, cover any communication participants, including those who turn out to be casual listeners. In addition, asubjectivation manifests itself as a requirement for the speaker to perform the illocutionary act “informative”, addressed to all participants in communication together, and at the same time — the speech act “message”, which regulates adequate interaction with the recipients of speech when using the language in the sermon. As a material, the authors considered statements built on the grammatical base of sentences with propositional (complex with additional clauses) and non-propositional meanings (impersonal with a due predicate). The relevance of the research is associated with the study of a new type of relationship in the semantic-syntactic structure of the sentence. The concept of asubjectivation allows us to formulate principles that regulate the features of referential relations in the structure of a sentence, taking into account the specifics of discourse.